Obtaining Active Polylactide (Pla) and Polyhydroxybutyrate (Phb) Blends Based Bionanocomposites Modified with Graphene Oxide and Supercritical Carbon Dioxide (Scco2)-Assisted Cinnamaldehyde: Effect on Thermal-Mechanical, Disintegration and Mass Transport Properties - Guarda-Moraga, A; Bruna-Bugueno, J; Romero-Figueroa, J; Rojas-Sepulveda, A; Torres-Mediano, A; Villegas-Vallejos, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Bionanocomposites based on Polylactide (PLA) and Polyhydroxybutyrate (PHB) blends were successfully obtained through a combined extrusion and impregnation process using supercritical CO2 (scCO2). Graphene oxide (GO) and cinnamaldehyde (Ci) were incorporated into the blends as nano-reinforcement and an active compound, respectively, separately, and simultaneously. From the results, cinnamaldehyde quantification values varied between 5.7% and 6.1% (w/w). When GO and Ci were incorporated, elongation percentage increased up to 16%, and, therefore, the mechanical properties were improved, with respect to neat PLA. The results indicated that the Ci diffusion through the blends and bionanocomposites was influenced by the nano-reinforcing incorporation. The disintegration capacity of the developed materials decreased with the incorporation of GO and PHB, up to 14 and 23 days of testing, respectively, without compromising the biodegradability characteristics of the final material. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.